2023
DOI: 10.1002/smll.202303192
|View full text |Cite
|
Sign up to set email alerts
|

Co/CoS2 Heterojunction Embedded in N, S‐Doped Hollow Nanocage for Enhanced Polysulfides Conversion in High‐Performance Lithium–Sulfur Batteries

Ming Zheng,
Junzhe Zhao,
Wei Wu
et al.

Abstract: Modulating the electronic configuration of the substrate to achieve the optimal chemisorption toward polysulfides (LiPSs) for boosting polysulfide conversion is a promising way to the efficient Li–S batteries but filled with challenges. Herein, a Co/CoS2 heterostructure is elaborately built to tuning d‐orbital electronic structure of CoS2 for a high‐performance electrocatalyst. Theoretical simulations first evidence that Co metal as the electron donator can form a built‐in electric field with CoS2 and downshif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…26,27 Zeolitic imidazolate framework-67 (ZIF-67), which is composed of metal ions (Co 2+ ) and an organic compound (2-methylimidazole), is a popular type of MOF. 28 In recent years, ZIF-67 derived carbon materials 29 with Co-based compounds, such as elemental cobalt, 30,31 cobalt oxide, 32,33 cobalt sulfide, 34,35 and cobalt selenide, 36,37 have been widely used as sulfur host materials and separator modifiers for LSBs. They not only have a strong chemical adsorption to LiPSs but also effectively accelerate the kinetics of the LiPS reaction process, so as to improve the electrochemical performance of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Zeolitic imidazolate framework-67 (ZIF-67), which is composed of metal ions (Co 2+ ) and an organic compound (2-methylimidazole), is a popular type of MOF. 28 In recent years, ZIF-67 derived carbon materials 29 with Co-based compounds, such as elemental cobalt, 30,31 cobalt oxide, 32,33 cobalt sulfide, 34,35 and cobalt selenide, 36,37 have been widely used as sulfur host materials and separator modifiers for LSBs. They not only have a strong chemical adsorption to LiPSs but also effectively accelerate the kinetics of the LiPS reaction process, so as to improve the electrochemical performance of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…To address the above problems, considerable efforts are proposed. One of the most popular strategies is incorporating sulfur into the carbon matrix, which provides a highly conductive pathway for rapid electron/lithium-ion transport as well as effective interaction with lithium polysulfides (LiPSs). However, owing to the weak affinity between the polar LiPSs and nonpolar carbon material, the capture ability for LiPSs is not enough, which cannot acquire a stable sulfur electrode. , Recently, researchers have found that polar metal oxides can be beneficial for anchoring the LiPSs by chemical immobilization. Compared with single metal oxides, multicomponent metal oxides such as ZnCo 2 O 4 and NiFe 2 O 4 are confirmed as more effective catalytic centers owing to the synergistic effects of the different metal ions. , In terms of the contribution of multicomponent metal oxides, a new class of high-entropy oxides (HEO) with the features of single-phase and entropy-stabilized crystalline comes into being.…”
Section: Introductionmentioning
confidence: 99%